Nitrous Oxide–Induced Neurologic Deficits: A Case Report - Siyuan Yang; Sarah Strube (Annals of Internal Medicine: Clinical Cases)
A 22-year-old man presented to the emergency department with a 1-week history of severe ataxia, inability to walk, and symmetrical bilateral upper- and lower-extremity paresthesia. Magnetic resonance imaging of the C-spine showed diffuse elevated T2 signal in the dorsal columns. Axial view of the C-spine revealed a lesion in the dorsal column that was hyperintense on T2-weighted images; this finding is called the “inverted V sign,” that is typically seen in subacute combined degeneration.